Communication des entreprises et des institutions : un regard médiéval - Sylvie Fabre (Communiquer)
The present review discusses the book Communication des entreprises et des institutions : un regard médiéval (2015) written by Martine Bocquet. This work derives from the doctoral thesis of the author, and grapples with restoring what it is that contemporary communication owes to the Middle Ages. It shows, in an original way, the deep benefit that communication studies and information sciences can expect from a return to the study of medieval culture.